Polyphosphate protects bacillus thuringiensis cells against reduced internal pH - Doruk, Tugrul; Demir, Zeynep; Gedik, Sedef Tunca (Elsevier Science Bv, 2012)
[No abstract available]
Keywords: Bacillus thuringiensis; Acid tolerance; Polyphosphate; rpoS; Polyphosphate kinase